THE MINORITY STRESS THEORY IN AN LGBTQIAPN+ SUPPORT GROUP: COPING STRATEGIES AND TERRITORIALIZATION - Gaspar, Aléxia de Carvalho (2025)
This study, based on the Minority Stress Theory (MST), investigates the biopsychosocial experiences of vulnerability experienced by participants of the (SOBRE)VIVER project, a psychological support group for the LGBTQIAPN+ community. Focusing on processes such as imposed stigma, internalized homonegativity, and identity concealment, the research seeks to understand how these experiences affect the mental health of this population. To this end, through a qualitative and descriptive approach, five LGBTQIAPN+ individuals participating in the project were selected for semi-structured interviews. Data analysis, conducted through thematic analysis of the interviews, revealed four main themes: the expressive and symbolic violence of stigma, the oppressive configurations that internalized LGBTphobia can exert, the redefinition of LGBTQIAPN+ territorialities in the face of identity concealment, and the importance of an affirmative network as a zone of collective resistance and mutual support. In this way, the research offers new perspectives on how vulnerabilities operate among gender and sexual minorities, bringing to light direct accounts of these experiences, often underrepresented in Brazilian MST research, and can contribute to strengthening support practices in mental health services through affirmative care strategies that consider the specificities of these minorities.